LI-RADS v2018 major criteria: Do hepatocellular carcinomas in non-alcoholic steatohepatitis differ from those in virus-induced chronic liver disease on MRI?. Issue 138 (May 2021) - Barat, Maxime; Nguyen, Thi Thuy Linh; Hollande, Clémence; Coty, Jean-Baptiste; Hoeffel, Christine; Terris, Benoit; Dohan, Anthony; Mallet, Vincent; Pol, Stanislas; Soyer, Philippe
Highlights: Hepatocellular carcinoma in non-alcoholic steatohepatitis shows MRI features similar to those of virus-induced chronic liver disease. The LIRADS v2018 major criteria have a high inter-reader agreement for hepatocellular carcinomas developing in non-alcoholic steatohepatitis. The LI-RADS v2018 major criteria can be applied in patients with non-alcoholic steatohepatitis. Abstract: Purpose: LI-RADS v2018 diagnostic system is used to diagnose hepatocellular carcinoma (HCC) in at risk patients. However, its applicability to HCC in non-alcoholic steatohepatitis (NASH) has not been specifically studied. The purpose of this study was to assess the applicability of LI-RADS v2018 diagnostic system for HCC in patients with NASH. Materials and methods: The MRI examinations of 41 patients with HCC and NASH (NASH group) were reviewed and compared to those obtained in 41 patients with HCC and virus-induced chronic liver disease (Virus group). MRI examinations of the two groups were compared for imaging presentation, LI-RADS major criteria and LI-RADS categorization. Qualitative variables were compared using Fisher exact test and quantitative variables using Mann-Whitney U test Interreader agreement was assessed using kappa statistic. Results: No significant differences in qualitative and quantitative variables were observed between the two groups. Most common findings in the two groups were hyperenhancement during the arterial phase and visibility on T2-weighted images (93 % vs . 98 %, P = 0.616 and 85 % vs . 88 %, P = 1.000 for NASH group and Virus group, respectively). No differences in prevalence between the two groups were found for any major LI-RADS v2018 criterion. Interreader agreement for LI-RADS categorization was strong for the NASH group (kappa = 0.802) and moderate for the virus group (kappa = 0.720). No differences were found between the two groups for LI-RADS categories ( P  =  0.303). Conclusions: The LI-RADS v2018 diagnostic algorithm can be applied in patients with NASH.